Assessment or Surveillance? Panopticism and Higher Education - Hyslop-Margison, Emery; Rochester, Ramonia (Philosophical Inquiry in Education, 2016)
In this paper, we explore Jeremy Bentham’s panopticon and consider its possible contribution to understanding more fully the impact of current assessment protocols and practices within higher education. More pointedly, we ask the following question: Are the plethora of assessment practices within higher education actually designed to improve student academic experience, or are they instead mechanisms of surveillance intended to control, dominate and invoke paranoia among university workers? In response to this question, we argue that the prevailing preoccupation with assessment in U.S. universities is motivated less by a genuine desire to enhance the actual academic experience of students than it is to offer hegemonic interests a psychological instrument of control to eliminate potential dissent over neo-liberal and managerial class imposed policies. To illustrate our central claim, we first review some general details of Bentham’s panopticon. Secondly, we briefly discuss Foucault’s analysis of the panopticon and consider his accompanying postulate on the tendency of individuals to self-regulate their behavior according to externally imposed and monitored expectations. We also examine in greater depth the relationship between the panopticon and the Lacanian gaze, with a focus on considering the latter’s psychological impact. Finally, we contend that the prevailing obsession with assessment in universities is a mechanism of institutional control that hinders rather than enhances the academic quality of contemporary higher education by limiting the scope of academic dialogue, social imagination and democratic structural critique.